Identifying the Potential Mechanism of Action of SNPs Associated With Breast Cancer Susceptibility With GVITamIN - Nguyen, An-phi; Nicoletti, Paola; Arnol, Damien; Califano, Andrea; Rodríguez Martínez, María (Frontiers in Bioengineering and Biotechnology, 2020)
In the last decade, a large number of genome-wide association studies have uncovered many single-nucleotide polymorphisms (SNPs) that are associated with complex traits and confer susceptibility to diseases such as cancer. However, so far only a few heritable traits with medium-to-high penetrance have been identified, the vast majority of the discovered vari- ants only leading to disease in combination with other still unknown factors. Furthermore, while many studies have aimed to link the effect of SNPs to changes in molecular pheno- types, the analysis has been often focused on testing associations between a single SNP and a transcript, disregarding hence the dysregulation of gene regulatory networks that has been shown to play an essential role in disease onset, notably in cancer. Here we take a systems biology approach and develop GVITamIN (Genetic VarIaTIoN functional analysis tool), a new statistical and computational approach to characterize the effect of a SNP on both genes and transcriptional regulatory programs. GVITamIN exploits a novel statistical approach to combine the usually small effect of disease-susceptibility SNPs, and reveals important oncogenic mechanisms, hence taking one step further in the direction of understanding the SNP mechanism of action. We apply GVITamIN on a breast cancer cohort and identify well-known cancer-related transcription factors, such as CTCF, LEF1, and FOXA1, as TFs dysregulated by breast cancer-associated SNPs. Furthermore, our results reveal that SNPs located on the RAD51B gene are significantly associated with an abnormal regulatory activity, suggesting a pivotal role for homologous recombination repair mechanisms in breast cancer.